DAMPAK KOLONIALISME BELANDA TERHADAP KEHIDUPAN SOSIAL - EKONOMI MASYARAKAT INDONESIA - Sihotang, Ellen Christy; Muhammad Fahrurozi; Damanik, Muhammad Fauzi; Pardosi, Christian Salomo; Tanjung , Flores (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The long period of Dutch colonial rule in Indonesia significantly influenced the formation of the nation’s socio-economic structure, creating patterns of dependency and inequality that continued to shape society. This historical reality underlies the importance of examining the impact of Dutch colonialism on the socio-economic life of Indonesian society. The purpose of this study is to analyze how colonial economic and social policies transformed indigenous economic systems and social structures. This research employs a library research approach by reviewing relevant books, scientific journals, and historical documents. The findings indicate that Dutch colonial policies, including trade monopolies, forced labor, agrarian regulations, and export-oriented economic systems, shifted traditional subsistence patterns into a colonial economy serving European market interests. These policies resulted in structural poverty, economic dependency, and sharp social stratification dividing society into Europeans, Foreign Orientals, and indigenous groups. Although colonial modernization introduced infrastructure development, it did not improve indigenous welfare. Instead, prolonged socio-economic pressures fostered collective awareness and resistance movements that later contributed to the emergence of national consciousness. Therefore, Dutch colonialism produced systemic socio-economic transformations while simultaneously shaping the foundation of Indonesia’s national awakening.